Focusing on Emotional and Social Intelligence Stimulation of People With Dementia by Playing a Serious Game—Proof of Concept Study - Berenbaum, Rakel; Tziraki, Chariklia; Baum, Reem; Rosen, Adi; Reback, Tuvia; Abikhzer, Judith; Naparstek, Daphna; Ben-David, Boaz M. (Frontiers in Computer Science, 2020)
Context: Dementia is one of the top five chronic diseases, which has an overwhelming impact on patients' life quality, family, and caregivers. Currently, research relating to people with dementia (PwD) focuses on the deterioration of cognitive abilities. A more innovative approach, and the one taken by this paper, is focusing on methods to maintain and improve functionality, communication and quality of life of PwD by building on remaining capacities in the yet unexplored domain of emotional and social intelligence (ESI). The use of serious games for PwD (SG4D) aimed at building social and emotional capacity is a budding field of research. Objectives: Proof of concept that the, low cost, easy to deploy SG4D, called “My Brain Works” (MBW), co-designed with PwD, enhances ESI, based on the Bar-On ESI model. Methods: 27 PwD, clients at MELABEV dementia day center, participated in a mixed methods 12 weeks pilot, proof of concept study using a tablet SG4D co-designed with PwD. Quantitative performance data was collected automatically by the tablet during game sessions. In this paper we focus on the analysis of the qualitative and quantitative data related to ESI, observed by 10 different researchers, during each game session. Results: Quantitative data revealed: both the PwD with high and low MoCA scores had similar average ESI scores. Qualitative analysis revealed that the PwD demonstrated 9 sub-components of the Bar-On ESI Model. Conclusion: While there is no drug to stop cognitive decline associated with dementia, interventions related to ESI, on the other hand, may improve functioning and quality of life. Despite declines in cognitive abilities, our study shows that a tablet based SG4D can stimulate their ESI and evoke responses in self-awareness, empathy, social and communication capacities. Using SG4D to exercise and maintain social skills is an area that may be promising in the future and may help counter the negative effects of social isolation and loneliness. Such games, while not focusing on cognitive improvement, may also impact on cognitive functioning and help bridge the gap between caregiver and PwD. More research is needed with larger sample sizes.